(untitled) (Revista de Investigación Intercultural ASAMPITAKOYETE, 2025)
The aim of this study was to evaluate the effect of the aeration system on the physiological and productive parameters of Piaractus brachypomus (paco). 30,000 specimens were used, with initial weight and length of 44.63 to 45.50 g and 13.35 to 13.68 cm, respectively. A completely randomized design (CRD), two treatments (T1: turbine aerator and T2: paddle aerator) and three replications were applied. 5,000 juveniles were stocked per earthen pond at a density of 3 fish/m2. Biometric sampling was performed monthly, and physiological sampling was performed at the beginning and end of the study. Blood parameters were analyzed by caudal artery puncture. Final weights and lengths per treatment were: T1: 339 g and 26.51 cm; T2: 389.33 g and 27.74 cm, with no significant difference (p: >0.05). There were no variations in daily feed intake, daily weight gain, specific growth rate (SGR), biomass, feed conversion ratio, condition factor (K) and species survival. The hematological parameters did not present alterations in the culture, but there were differentiated levels of hemoglobin (Hb), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC). Cortisol presented differentiated levels but did not show alterations in the behavior of the species. The aeration system has a positive effect on the physiological and productive parameters of Piaractus brachypomus (paco) culture.